Uji Toksisitas Subakut Ekstrak Etanol Daun Asam Jawa Dosis Efektif Sebagai Antihiperglikemia Terhadap Kadar AST, ALT, dan Kreatinin Tikus (Rattus norvegicus) - Sitti Rahimah Rachman; Dzulkifli Dzulkifli; Suwahyuni Suwahyuni; Rahmad Aksa; Mirnawati Salampe; Akbar Awaluddin (Jurnal Farmasi Indonesia, 2021)
The toxicity test is one of the pharmacological testing stages that must be carried out to assess the use of a drug. Research on the activity test of the ethanol extract of Tamarind leaves (Tamrindus indica L) at a dose of 14 mg / 200 g BW as an antihyperglycemia in experimental animals gave results that were not significantly different from the standard drug activity of Glibenclamide as an antidiabetic mellitus, so this study was conducted with the aim of looking at the ethanol of tamarind leaves. (Tamrindus indica L) for 30 days on levels of the enzymes AST, ALT, and creatinine in rats (Rattus norvegicus). This sub-acute toxicity test used 14 test animals divided into 2 groups, each group consisting of 7 rats. Group I was given 0.5% Na CMC treatment as a control and group II was treated with the ethanol extract of tamarind leaves at a dose of 14 mg / 200 g BW for 30 days. On the 31st day, blood serum measurements were taken with AST, ALT and creatinine parameters using a humalyzer. The results of the subacute toxicity test showed that giving tamarind leaves ethanol extract as an antihyperglycemia did not cause an increase in the AST, ALT AND creatinine enzymes beyond normal limits.